Pattern of aerobic bacteria with antimicrobial susceptibility causing community acquired urinary tract infection - Parvin, Ummey Shahnaz; Hossain, MA; Musa, AK; Mahamud, C; Islam, MT; Haque, N; Muhammad, N; Khan, SI; Mahmud, NU (Mymensingh Medical Journal, 2009)
Mymensingh Med J. 2009 Jul;18(2):148-53. The abstract of this article is available on the PubMed website